Qurʾānic Interpretative Latitude and Human Evolution: A Case Study - Majid, DS Adnan (Al-Bayān, 2014)
Muslims today employ various and often conflicting strategies to mitigate contradictions between traditional Islamic teachings and modern science, especially in matters related to the age of the universe and the origin of humans. On the one hand, any scientific theory deemed problematic might be rejected outright; on the other, Islamic texts may be reinterpreted to fully support a novel scientific theory. There is, however, an alternative hermeneutical approach that uses intra-textual analysis to acknowledge “interpretative latitude” in the Qurʾān and other Islamic texts – the possibility that these texts allow for ambiguity and multiple interpretations that may or may not agree with modern science. In this paper, human evolution will serve as a case study of the implementation of this approach via a structured discussion of common Muslim objections to the theory. The paper will conclude with a discussion of the implications of this approach on defining the role of the Qurʾān and on the boundaries of religion and science.